‘No one gives you a chance to say what you are thinking’: finding space for children’s agency in the asylum system - Heaven Crawley (Area, 2009)
Drawing on research undertaken with separated children seeking asylum in the UK, this paper explores the ways in which children's political identities and experiences have been conceptualised in procedures for determining who is – and is not – in need of protection under international refugee law. The paper focuses in particular on the experiences of separated children during the asylum interview. It is suggested that the conduct of the interview not only indicates a basic lack of humanity and care in engaging with the experiences of separated asylum-seeking children, but also a particular conceptualisation of ‘childhood’ that undermines the ability of children to fully articulate their experiences and to secure access to the protection to which they are entitled. The consequence of this approach is not only that separated asylum-seeking children are significantly less likely than adults to be granted refugee status, but that children who express political views and agency may not be considered to be children at all.